The effect of supplemental fat and lysine on finishing pig performance and carcass characteristics - Friesen, K.G.; Thaler, R.C.; Goodband, Robert D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred and sixty pigs averaging 127.4 lb were used to determine the benefit of 5% supplemental fat and (or) .20% lysine on growth performance and carcass characteristics. The trial consisted of four treatments: 1) a .61 %, lysine milo-soybean meal control diet; 2) control + 5% fat; 3) control + .20% lysine; 4) control + 5% fat and .20% lysine. Lysine:metabolizable energy ratios were held constant at 1.91: 1 for treatments 1 and 2 and at 2.52: 1 for treatments 3 and 4. Pig weights and feed consumption were recorded every third wk to calculate average daily gain (ADG), average daily feed intake (ADFI), and feed/gain (F/G). At the termination of the experiment, pigs were scanned via ultrasound for 10th rib backfat thickness (BF) and loineye area (LEA). High and low ambient temperatures were monitored to evaluate growth performance relative to temperature. Improvements in feed efficiency were detected when supplemental fat was added to the diet from d 0 to 21. During this period, the average temperature fluctuated from a low of 67.4F to a high of 93.4 F. This period was the hottest of the experiment, with a mean temperature of 80.4°F for 16 d. Average daily gain increased 5 to 8% with supplements of fat or the combination of both fat and lysine to the diet. From d 21 to 42, no differences in performance were detected for diets supplemented with fat and(or) lysine. Overall, supplemental fat tended to improve feed efficiency by 8 to 14% in control and lysine-supplemented diets, respectively. Differences in ADG and ADFI were not detected over the entire trial. Supplemental fat increased BF and tended to reduce LEA. Supplemental lysine increased LEA with no effect on BF. These data suggest that supplemental fat and (or) lysine can be beneficial during periods of temperature above 90F. Once temperatures subsided, a benefit to supplementing lysine in combination with fat was not detected.
Keywords: Swine; Performance; Fat; Lysine; G-F